Effect of Ralgro on the performance of cull beef cows - L.R. Corah; F. Brazle; J.D. Dawes (Kansas Agricultural Experiment Station Research Reports, 1980)
We assigned 110 cull beef cows of mixed breeding to a control group and a group implanted with 36 mg Ralgro. Ralgro implants improved gains 12.8 lbs (11.2%) over a 59-day grazing period.
Keywords: Cattlemen& #x27; s Day; 1980; Report of progress (Kansas State University. Agricultural Experiment Station); 377; Beef; Performance; Cull beef cows